Effects of the Health Belief Promotion Program on COVID-19 Preventive Behavior among Medical Patients in a University Hospital - Janpanya, Kanjana; Klunklin , Pimpaporn; Lertwatthanawilat, Wanchai (Journal of The Royal Thai Army Nurses, 2025)
This quasi-experimental research used two groups to measure the antecedents. The objective was to study the effect of the health belief promotion program on COVID-19 prevention behavior among 52 patients from medical wards, with 26 patients in the experimental group and 26 in the control group. The research instruments for data collection were questionnaires on demographic information and COVID-19 prevention behavior for medical patients in a university hospital. Data were analyzed using descriptive statistics, Wilcoxon signed rank test, and Mann-Whitney U test. The results of the study found that the experimental and control groups were in the age range of 61 years and were equally female and male. Most have primary school. There is a congenital disease. Most cardiovascular system diseases and most of them had received the COVID-19 vaccine after receiving the program within 4 weeks, the experimental group’s median practice scores increased from 32.00 points to 36.00 points (out of 40 points) (p<.001). This improvement was not observed in the control group, whose median practice score remained statistically unchanged at 32.50 points. While the median practice scores between the groups, both before and after, were not significantly different, the overall outcome suggests that the Health Belief Promotion Program on COVID-19 prevention practices could be a valuable tool in preventing respiratory infections in other groups of patients with emerging and re-emerging diseases that have the same mode of transmission.